Anagliptin and sitagliptin as add‐ons to metformin for patients with type 2 diabetes: a 24‐week, multicentre, randomized, double‐blind, active‐controlled, phase III clinical trial with a 28‐week extension. Issue 5 (14th January 2015) - Jin, S.‐M.; Park, S. W.; Yoon, K.‐H.; Min, K. W.; Song, K.‐H.; Park, K. S.; Park, J.‐Y.; Park, I. B.; Chung, C. H.; Baik, S. H.; Choi, S. H.; Lee, H. W.; et al.
<x xml:space="preserve">Abstract</x> We conducted a 24‐week, multicentre, double‐blind, randomized study with a 28‐week extension to compare the efficacy and safety of anagliptin and sitagliptin as an add‐on to metformin in patients with type 2 diabetes. Patients inadequately controlled on metformin were randomized to either anagliptin (100 mg twice daily, n = 92) or sitagliptin (100 mg once daily, n = 88). The primary endpoint was the change in glycated haemoglobin (HbA1c) from baseline to week 24. The mean changes in HbA1c were −0.85 ± 0.70% (p < 0.0001) for anagliptin and −0.83 ± 0.61% (p < 0.0001) for sitagliptin, with a mean difference of −0.02% (95% confidence interval of difference, −0.22 to 0.18%). In both groups, the fasting proinsulin : insulin ratio significantly decreased from baseline, with improved insulin secretion. Safety profiles were similar in each group. In conclusion, the non‐inferiority of the efficacy of anagliptin to sitagliptin as an add‐on therapy was established with regard to efficacy and safety.